10.1016/S0271-7964(08)70538-X (CrossRef Listing of Deleted DOIs, 2000)
AIM: The aim of this research was to explore what makes (or would make) for good genomic care delivered wholly or in part by paediatricians. METHODS: An interpretive description, qualitative study with parents of children offered genomic testing as an outpatient for a condition other than cancer; general and subspecialist paediatricians; nurses; and genetic counsellors. Data were primarily collected retrospectively and analysed using inductive content analysis. Interpretation was enriched by the involvement of parent and paediatrician project advisors. RESULTS: Twenty-five parents and 20 health professionals participated. Most parents had received a genetic diagnosis for a child presenting with neurodevelopmental delay and/or epilepsy. Key aspects of good genomic care identified included: adopting a slow, multi-appointment approach to discussing genomic testing in certain instances; letting families know what to expect; signposting to information and psychosocial support services when disclosing results; communicating next steps; and adopting a team approach to aid sense-making. Paediatricians were not expected to do everything, with ongoing roles for genetic experts described. At different stages of the testing process, paediatricians existing and ongoing relationships with families were identified as an asset in helping promote good experiences. CONCLUSION: Genomic testing in usual paediatric outpatient care can be delivered well, with this research yielding practical guidance for paediatricians. Ongoing evaluation as models of care evolve will support the delivery of high-quality genomic care that best meets families' needs.